2017
DOI: 10.1111/1751-2980.12544
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based survey of knowledge of, attitudes to and practice of colorectal cancer screening in Hong Kong

Abstract: To reduce the morbidity and mortality of CRC significantly, average risk and high-risk groups should be encouraged to come forward for screening even if they are asymptomatic. Educating the population, simplifying the screening procedure and offering financial support by the government are keys to success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Even the percentage of those who desired to undergo CRC screening (43.6%) was lower than the desired coverage rate in our study. Reasons such as not believing to be at risk, lack of knowledge about the tests, lack of someone recommending the test, being afraid of a cancer diagnosis, embarrassment and being afraid of painful procedures have been listed as the reasons why individuals do not undergo a CRC screening test in various studies (Bocci et al, ; Harewood et al, ; Koo et al, ; Pontone, ; White et al, ; Wong et al, ). The reasons for not undergoing a CRC screening test were also similar in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even the percentage of those who desired to undergo CRC screening (43.6%) was lower than the desired coverage rate in our study. Reasons such as not believing to be at risk, lack of knowledge about the tests, lack of someone recommending the test, being afraid of a cancer diagnosis, embarrassment and being afraid of painful procedures have been listed as the reasons why individuals do not undergo a CRC screening test in various studies (Bocci et al, ; Harewood et al, ; Koo et al, ; Pontone, ; White et al, ; Wong et al, ). The reasons for not undergoing a CRC screening test were also similar in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The study data were collected with the ‘Data Collection Form' created by the authors after reviewing the relevant literature (Bocci, Troiano, Messina, Nante, & Civitelli, ; Harewood et al, ; Teixeira et al, ; Wong et al, ) and the ‘Health Belief Model Scale for Protection from Colorectal Cancer (HBMSPCC)'. We used 17 questions related to the socio‐demographic characteristics (such as age, gender, educational level, marital status, perceived income, social security coverage, personal habits, chronic diseases, history of cancer, body mass index [BMI]) and 15 questions related to their CRC risk knowledge and behaviour (such as those related to CRC risk, symptoms and screening status) for a total of 32 questions in the data collection form.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…91.5% responded that there wasn't any case of CRC in their family. 13 In another study conducted among English population showed that only 10% of the participants were aware of the fact that CRC is ranked third among common type of cancers and merely 46% people knew some symptoms and risk factors of CRC. 14 There is another study regarding the awareness of CRC among the population of Perak state of Malaysia, and this study illustrated that 38% people had no knowledge regarding CRC.…”
mentioning
confidence: 99%